INTERMEDIATE TIER FOR GNU PROLOG - PHP INTEGRATION - Rafał Szklarczyk (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The paper provides a concept of GNU-Prolog integration with PHP using ANSI C socket server as a middleware [8]. There are a few methods of integration of web programming together with CLP proposed so far. The simplest and the most obvious way is to run CLP program in CGI mode, but it has its disadvantages as well. For some appliance CLP programs can have long execution time that could cause web server timeouts. For that reason a new approach is proposed: to separate user interface (web based) from CLP program execution. That goal is achieved by means of socket server written in ANSI C. The socket server controls the execution of the main program and communicates with the GUI application to send the results. According to what was said above, the logic part is run as GNU-Prolog process and the GUI is built with PHP.